Quantifying the Local Effect of Northern Hemisphere Atmospheric Blocks on the Persistence of Summer Hot and Dry Spells - Röthlisberger, Matthias; Martius, Olivia (Geophysical Research Letters, 2019)
The persistence of heat waves and droughts is a key factor in determining their societal impact. Here, the local effect of atmospheric blocks on the persistence of summer hot and dry spells is quantified by comparing their climatological daily survival probability, that is, the probability to survive the next day, to their daily survival probability when they co‐occur with a block. The survival odds of hot spells are increased by more than 50% over most of the Northern Hemisphere extratropical land masses when co‐occurring with blocks. Dry spell persistence is also strongly increased by colocated blocks over western North America, Europe, and southern Russia, while it is significantly decreased over the western North Atlantic and the western North Pacific. These spatial differences in the effect of blocks on both spell types are explained by considering the spatially varying surface temperature and precipitation anomalies induced by the blocks.